Acute myocardial infarction with multiple coronary thromboses in a young addict of amphetamines and benzodiazepines - Al Shehri, Mohammed A (Journal of the Saudi Heart Association, 2016)
A 35-year-old man of average build and a smoker, with a background of a psychiatric disorder, was brought by his neighbor to the emergency department after an hour of severe chest pain. Upon arrival at the hospital he had cardiac arrest, was resuscitated, and moved to the catheterization laboratory with inferior, posterior, and lateral myocardial infarction. Coronary angiography showed an unusual thrombosis in multiple coronary branches. Toxicology report showed high levels of amphetamines and benzodiazepines in the patient's original blood sample. The patient was kept under ventilation for 18 days, with difficult recovery due to severe withdrawal manifestations, ventilation acquired pneumonia, and rhabdomyolysis inducing acute renal failure. The patient regained near normal left ventricular function after baseline severe regional and global dysfunction. We postulate a relationship between the use of amphetamines, potentiated by benzodiazepines, and occurrence of acute thrombosis of multiple major coronary arteries